Developing thinking skills and attitude among grade four pupils using a module on the concept environment - Obong, Mercedes Isidro 1931- (1977)
The study proposed a module to develop thinking and attitude skills for individualizing instruction in grade four. It is a device by which the students can study a unit on social studies at their own rate, with little or no help from th teacher. The module was based on the new Scope and Sequence of the Social Studies for Elementary Schools issued by the Department of Education. Social Studies being interdisciplinary involves many disciplines to carry out the concepts. The concept is on Environment discussed in the discipline of Geography.
Vita.
Thesis (Master of Arts (Social Studies Education))--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Elementary) -- Philippines -- Calbayog City (Samar); Teaching -- Philippines -- Calbayog City (Samar) -- Aids and devices; Individualized instruction -- Philippines -- Calbayog City (Samar); Thought and thinking